-7(-4y-19)+15=-2(-9y+16)

Simple and best practice solution for -7(-4y-19)+15=-2(-9y+16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-4y-19)+15=-2(-9y+16) equation:


Simplifying
-7(-4y + -19) + 15 = -2(-9y + 16)

Reorder the terms:
-7(-19 + -4y) + 15 = -2(-9y + 16)
(-19 * -7 + -4y * -7) + 15 = -2(-9y + 16)
(133 + 28y) + 15 = -2(-9y + 16)

Reorder the terms:
133 + 15 + 28y = -2(-9y + 16)

Combine like terms: 133 + 15 = 148
148 + 28y = -2(-9y + 16)

Reorder the terms:
148 + 28y = -2(16 + -9y)
148 + 28y = (16 * -2 + -9y * -2)
148 + 28y = (-32 + 18y)

Solving
148 + 28y = -32 + 18y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-18y' to each side of the equation.
148 + 28y + -18y = -32 + 18y + -18y

Combine like terms: 28y + -18y = 10y
148 + 10y = -32 + 18y + -18y

Combine like terms: 18y + -18y = 0
148 + 10y = -32 + 0
148 + 10y = -32

Add '-148' to each side of the equation.
148 + -148 + 10y = -32 + -148

Combine like terms: 148 + -148 = 0
0 + 10y = -32 + -148
10y = -32 + -148

Combine like terms: -32 + -148 = -180
10y = -180

Divide each side by '10'.
y = -18

Simplifying
y = -18

See similar equations:

| 0.5+2x=3x-0.5 | | 6x^4-12x^3+18x^2=0 | | 27x-35=105 | | x-.2=96 | | 2x+3(-4)=-4 | | 22x+25=6(3x+3)+4x+7 | | 4y-9=5y-5 | | 11v-8v=18 | | 2x-54y=-15 | | -2x-3(-6x-11)=-7 | | 59=x+(x+5)+(x+9) | | 5(3+1)(m-5)= | | 27-(-4)+2= | | 5b+3-2b=12 | | 3(2x-8)-(3X-2)=15 | | 2y=2+8 | | 4y+10=4y-10 | | 20x+23y+24z=185 | | -3(t-4)+9t=8t-3 | | x=.1(50+x) | | 7(x-10)=20-9x | | 2z+6+11z+7=90 | | 6z+12=5z+11 | | 3x-x-4x=18 | | -6(5+r)=12 | | 4s+3p=tp-3 | | (x^2)+2x+1=5 | | Solvex-8y=15fory | | S+s(3)=28 | | (2u)(3x^3)(7u^7x^3)=0 | | (2x+3)+(3x+2)=180 | | 4*2k=12 |

Equations solver categories